2020
DOI: 10.1186/s40545-020-00234-2
|View full text |Cite
|
Sign up to set email alerts
|

Registration and local production of essential medicines in Uganda

Abstract: Background: Universal access to high quality essential medicines is critical to sustainable development (SDG 3.8). However low-and middle-income countries struggle to ensure access to all medicines on their national essential medicines lists (EML). Market registration is the first step in determining both access and availability yet the extent to which essential medicines are registered for use at country level is not known. Companies apply for a marketing authorisation, however low price or lack of a market i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 9 publications
(11 reference statements)
0
28
0
1
Order By: Relevance
“…Finally, regular and transparent tracking, auditing, and reporting on product registrations in countries hosting trials could better help advance access to medicines and vaccines globally. 42 To aid in this process, it would be helpful to increase transparency around trial site locations.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, regular and transparent tracking, auditing, and reporting on product registrations in countries hosting trials could better help advance access to medicines and vaccines globally. 42 To aid in this process, it would be helpful to increase transparency around trial site locations.…”
Section: Discussionmentioning
confidence: 99%
“…However, reimbursement processes are increasingly critical in LMICs with respect to achieving UHC, which means financial risk protections and prevent the patient from incurring high out-of-pocket expenses for essential medicines. Several papers in our review described the high out-of-pocket costs for patients, regardless of whether medicines are listed on NMLs [ 20 , 22 , 39 , 45 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Brhlikova and colleagues found that in Uganda, following increases to government funding for essential medicines, demand for locally produced medicines also increased [ 47 ]. While adding drugs to a NML is a sign of increased priority by the government, pharmaceutical manufacturers may not necessarily respond unless other factors, such as the potential for profits, are addressed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was related to high workload, poor remuneration, and non-payment of stipends 36, 41, 75, 158 . Other barriers reported include non-payment of suppliers 70 and low tax incentives and subsidies to pharmaceutical companies 170 to support EML implementation.…”
Section: Resultsmentioning
confidence: 99%